Exploring Factors Affecting The Use of E-Learning on Quality of Learning Process in Private Universities - Baso, Andi Sabirin; Pakawaru, Muhammad Ilham; Nurlailah, Nurlailah (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this research is to analyze the relationship between perceived usefulness of e-Learning on quality of learning and e-Learning perceived ease of use on quality of learning. This research method is quantitative with a survey, the data used in this research is primary data. Data was obtained by giving online questionnaires to 400 private university lecturer respondents. determined by simple random sampling method. The questionnaire consists of three parts of questions where each part of the question represents a research variable. The first part contains questions related to moderator variables in this case in the form of respondent profiles, the second part deals with perceived usefulness variables, the third part deals with perceived ease of use variables, the fourth part deals with attitude and achievement variables. The questionnaire uses a Likert scale of 1 to 5 with a size from the lowest number which means strongly disagree (STS) to the highest number which means strongly agree (SS). Data analysis in this study used structural equation modeling (SEM) with SmartPLS 3.0 software tools. The stages of testing the data are testing the validity of the reliability and testing the hypothesis. The results of this study are e-Learning perceived usefulness has a positive and significant effect on the quality of learning, e-Learning perceived ease of use. has a positive and significant effect on the quality of learning.